2021
DOI: 10.1111/1744-1633.12479
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth practice in surgery: Ethical and medico‐legal considerations

Abstract: There was rapid growth of telehealth practice during the COVID‐19 outbreak in 2020. In surgery, there were beneficial effects in terms of saving time and avoiding physical contact between healthcare professionals and patients when using telehealth in the delivery of perioperative care. As telehealth is gaining momentum, the evolving ethical and medico‐legal challenges arising from this alternative mode of doctor–patient interaction cannot be underestimated. With reference to the “Ethical Guidelines on Practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…In a systematic review of 24 studies using telecommunications technologies in the field of surgical care, Asiri and collaborators concluded that the use of telemedicine had beneficial effects in preand post-operative examinations, including follow-up visits [2]. It was also particularly appropriate to use teleconsultation to provide patients with post-operative care for low-risk elective procedures [3,10].…”
Section: Telemedicine In Different Medical Specialtiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In a systematic review of 24 studies using telecommunications technologies in the field of surgical care, Asiri and collaborators concluded that the use of telemedicine had beneficial effects in preand post-operative examinations, including follow-up visits [2]. It was also particularly appropriate to use teleconsultation to provide patients with post-operative care for low-risk elective procedures [3,10].…”
Section: Telemedicine In Different Medical Specialtiesmentioning
confidence: 99%
“…Recent studies have shown that telemedicine, if used by the community, can lead to a significant improvement in patient management, long-term cost savings and greater sustainability for public health, even in developed countries. The current modalities for performing teleconsultation are: (i) real time, in which doctor and patient can interact with each other at the time of consultation and (ii) synchronous, where the patient answers question and the doctor responds later, according to his convenience via short message service (SMS) or e-mail [3][4][5][6][7]. The current COVID-19 outbreak has further reinforced the need for the use of remote consultation in order to reduce contact between patients and healthcare professionals to the bare minimum [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some institutions, clinical governance of these matters are rudimentary or scarce despite being HIPAA (Health Insurance Portability and Accountability Act)-compliant and stressed further by the rapidly moving, pandemic-related landscape. It is critical that surgeons worldwide proactively engage in developing guidelines and practices that remain consistent with existing medicolegal and ethical obligations [44] .…”
Section: Rise Of Telemedicine During the Pandemicmentioning
confidence: 99%
“…International standards have been defined to govern how confidentiality can be maintained through the use of telehealth services. 9 The surgeon must be aware of what can be constituted as medical records when legal issues arise.…”
mentioning
confidence: 99%